Implementasi Model Multiple Intelligence Pada Pembelajaran Ilmu Hadits di Kelas X MAN 4 Jombang - Al Ghozali, M. Dzikrul Hakim; assakina, nashiha (TARBAWI : Jurnal Pendidikan Agama Islam, 2024)
The purpose of this study is to reveal the implementation of learning hadith science using the multiple intelligence method in class X MAN 4 Jombang. The subjects of this study were students of MAN 4 Jombang. The approach used in this study is qualitative with a case study approach. Data collection techniques in this study were interviews, observations, questionnaires, and documentation. The data analysis technique is to collect data, reduce data, and draw conclusions. The results of the study show that by applying this multiple intelligence learning model, it can be seen that kinesthetic intelligence, linguistic intelligence, and intrapersonal intelligence are superior in the hadith science learning process. In addition, there are characteristics and learning models that are more appropriate to the intelligence possessed by each student so that the teacher's role in guiding students becomes very important and learning objectives can be achieved properly.